Fresh frozen plasma utilization pattern in tertiary care hospital of North Western India - Prinja, Nippun; Sharma, Sarita; Narain, Rachna (International Journal of Research in Medical Sciences, 2017)
Background: Fresh Frozen Plasma (FFP) is mainly used in treatment of coagulation derangements; trauma emergencies. It is the most inappropriately used blood component. Since the guidelines for FFP use in a clinical setting are not well defined, this study aims at defining the appropriateness of use of FFP in the light of its risks and adverse effect. Audit of institute FFP usage with specific aim of assessing appropriate use, based on clinical indications and laboratory parameters in requisition form. Methods: Retrospective analysis of 10,753 FFP supplied in 3072 patients from June 2016 to December 2016 in SMS Hospital, Jaipur, Rajasthan, India was done in Department of Immunohaematology and Transfusion Medicine, SMS Hospital, Jaipur, Rajasthan, India. Detailed analysis of clinical indication, INR value, specialty, age, gender of patient was done. Results: 10,753 FFP was supplied to 3072 Patients. 6990 FFP was supplied to 1995 males. 3763 FFP was supplied to 1077 females. Clinical use of FFP for medical and surgical conditions was highest seen in Blood Cancers (13%) and Cardiosurgery (22.3%). 15.2% was available from Emergency Department. 1.9% of FFP was returned back. Patients with Deranged Coagulation Profile (DCP) require maximum transfusion (49.3), Bleeding patients (37.6%), DIC (3.3%). FFP used for plasmapheresis (2.6%). No information available about diagnosis (7.2%) was available from Emergency Department. Conclusions: FFP is most inappropriately used blood component (39.57%) and should be used judiciously. Regular audit of blood components serves as tool for accomplishment of quality tools and to understand clinical transfusion practices.